(untitled) (Asian-Australasian Journal of Food Safety and Security, 2023)
Peda is a highly nutritious indigenous milk product of Bangladesh containing milk solids added sugar and other additive like cardamom powder. This experiment was conducted to test the feasibility of using mawa (dried milk) for making peda and also conducted to test the impact of sugar level on the quality of peda. Sugar, as traditional sweetener was used to make peda samples at the level of 0 g, 75 g, 150 g and 225 g. Peda samples were prepared with these different sugar ratios were analyzed for sensory attributes, chemical composition and microbiological quality. Analysis of the data for quality such as flavor, body and consistency, color and appearance and chemical analysis such as protein content, carbohydrate content, ash and total solids contents of peda samples revealed significant (P<0.05) difference, but there was no significant (P>0.05) differences for fat content and total viable count of peda samples. The organoleptic quality of 150 g sugar containing peda samples scored better result than control and other treatments. If overall quality aspects were considered, 150 g sugar containing peda samples gave best results than other samples. Asian Australas. J. Food Saf. Secur. 2023, 7 (2), 56-61